CXSense a scalable password-based key management scheme for mobile ad-hoc networks - Acang, James Patrick A. (College of Engineering, University of the Philippines Diliman, 2015)
In a dynamic, mobile ad-hoc network (MANET), nodes cooperatively participate to facilitate delivery of messages. Nodes establish links with other nodes, forming an arbitrary self-organized network where each node may route messages from the source to the destination. Since messages need to be passed from one node to the other before reaching the intended recipient, security becomes an important concern. A key ingredient to try and secure messages in a MANET is an efficient key management scheme. Most of the exisiting schemes, however, have relied on trusted third parties, certificate authorities, and more powerful nodes to facilitate key management. Moreover, these components may make MANETs restrictive, unscalable, impractical to implement, and may require the network to have centralized administration. This can negatively impact on the self-organization aspects of a MANET. We propose here a new key management scheme that follows the self-organization property of MANETs. This enables nodes to join and communicate freely without third party authorities to facilitate in the secured communication. We exploit here the characteristics of multicast communication to improve performance and to enhance scalability. We compared the performance of our scheme with two existing schemes via simulation. Our results show that our proposed scheme have performance gains over the existing schemes.